CYBER LEARNING AS A TRANSFORMATION OF LEARNING IN THE DIGITAL ERA - Masruri, Masruri; Zakaria, Nanang; Sobirin, Sobirin; Irwan, Irwan; Faisal, Muhammad (LP2M IAI Al-Khairat Pamekasan, 2024)
The aim of this research is to examine cyber learning as an educational transformation in the digital era. The research method used by the researcher is a qualitative research method with a library study type of research. The results of this research show that the implications of integrating technology into education are very broad and include several aspects such as pedagogy, student involvement, institutional structure, and societal considerations. Although the results of the literature review recognize the transformative potential of cyber learning, strategic planning, ongoing research, and strong policy development are needed to navigate the complexity of educational paradigms in the digital era. As progress continues, a deep understanding of the diverse interactions between technology and education is critical so that the benefits of cyber learning can be fully utilized by students, educators and society.